"The European Committee of Social Rights as a Monitoring Body in the System of the European Social Charter" - Gadkowski, Aleksander (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The aim of this article is to present the European Committee of Social Rights as a moni-toring treaty body in the system of the European Social Charter. The author pays par-ticular attention to the mechanism of collective complaints, which was introduced to the Charter’s supervisory system on the basis of the 1995 Additional Protocol. In the author’s opinion, on the basis of the competence of the European Committee of Social Rights to hear collective complaints, it is arguable that this important treaty body in the system of the European Social Charter performs the function of a quasi-judicial organ in the monitoring process, which distinguishes it from other treaty bodies in the field of the international protection of human rights